Impact of Smoking Intensity and Duration on Audiometric Thresholds and Sensorineural Hearing Loss: A Cross-Sectional Study among Adult Iraqi Males - Radhi, Noora Kareem; Dawood, Mohammed Radef (National Journal of Community Medicine, 2025)
Background: This cross-sectional study aimed to examine the effect of smoking intensity (pack-years) and duration on hearing thresholds and sensorineural hearing loss (SNHL) occurrence among adult Iraqi males. Methods: 100 males (50 smokers, 50 non-smokers), aged 18-45 years, were recruited at Mustansiriyah University, Baghdad, Iraq. Data collected from September 2024 to January 2025 included demographics, smoking history (pack-years), and nicotine dependence (Fagerström Test). Participants underwent otoscopic and physical examination, tympanometry, and pure-tone audiometry, measuring hearing thresholds at low frequencies (500-2000 Hz) and high frequencies (3000-8000 Hz). Logistic regression was used to assess smoking’s association with SNHL. Results: SNHL was detected in 16% of smokers and none of the non-smokers (p = 0.003). Multivariate analysis showed that smoking duration (AOR = 1.21; 95% CI: 1.04-1.45; p = 0.011) and pack-years (AOR = 1.38; 95% CI: 1.07-1.88; p = 0.021) independently predicted SNHL, after adjusting for age and occupation. Smokers had poorer hearing thresholds, especially at high frequencies (3000-8000 Hz). A smoking duration ≥24.5 years predicted SNHL with 87.5% sensitivity and 90.5% specificity, though this cutoff is exploratory due to the small number of SNHL cases (n=8). Fagerström Test results showed no significant association between nicotine dependence and SNHL. Conclusion: Smoking duration and intensity are associated with elevated hearing thresholds and high-frequency SNHL in adult males. The findings highlight smoking’s harmful auditory effects, but the small sample size and cross-sectional design limit causality. Generalizability may be limited as only male participants were included. Further longitudinal studies including both genders are needed to confirm these findings.